(untitled) (Journal of the College of Basic Education, 2026)
This study highlights the educational aspect in Islam and its role in shaping the contemporary Muslim, particularly in light of the numerous changes affecting Muslims and their religious lives today. All divine revelations have conveyed one ultimate truth — the greatest truth in existence — namely, the oneness of God (Tawhid). However, the methods and approaches of calling to this truth have varied from one prophet to another and from one nation to another, according to the diversity of human temperaments, thoughts, and circumstances. The final divine message, Islam, also adopted diverse methods in presenting this eternal truth, taking into account human nature and its innate inclinations. Among the most influential educational methods in Islam is the approach of encouragement and deterrence (Targhib and Tarhib), which plays a vital role in shaping the individual’s behavior. It appeals to one’s emotions, nurtures innate goodness, motivates righteous deeds and obedience, and deters wrongdoing and sin, thus achieving true happiness in both this life and the hereafter. The study comprises an introduction, a main chapter, and a conclusion, with the main chapter divided into two sections: Education through Qur’anic Dialogue. Education through Encouragement and Deterrence. The research concludes with the most significant findings derived from the study.